Nonsense-Mediated RNA Decay Factor UPF1 Is Critical for Posttranscriptional and Translational Gene Regulation in Arabidopsis. Issue 9 (14th July 2020) - Raxwal, Vivek K.; Simpson, Craig G.; Gloggnitzer, Jiradet; Entinze, Juan Carlos; Guo, Wenbin; Zhang, Runxuan; Brown, John W.S.; Riha, Karel
Abstract : The RNA helicase and ATPase UPF1 affects transcriptome homeostasis and gene expression through nonsense-mediated RNA decay, splicing, and translation in Arabidopsis. Abstract: Nonsense-mediated RNA decay (NMD) is an RNA control mechanism that has also been implicated in the broader regulation of gene expression. Nevertheless, a role for NMD in genome regulation has not yet been fully assessed, partially because NMD inactivation is lethal in many organisms. Here, we performed an in-depth comparative analysis of Arabidopsis ( Arabidopsis thaliana ) mutants lacking the NMD-related proteins UPF3, UPF1, and SMG7. We found different impacts of these proteins on NMD and the Arabidopsis transcriptome, with UPF1 having the biggest effect. Transcriptome assembly in UPF1-null plants revealed genome-wide changes in alternative splicing, suggesting that UPF1 functions in splicing. The inactivation of UPF1 led to translational repression, as manifested by a global shift in mRNAs from polysomes to monosomes and the downregulation of genes involved in translation and ribosome biogenesis. Despite these global changes, NMD targets and mRNAs expressed at low levels with short half-lives were enriched in the polysomes of upf1 mutants, indicating that UPF1/NMD suppresses the translation of aberrant RNAs. Particularly striking was an increase in the translation of TIR domain-containing, nucleotide binding, leucine-rich repeat (TNL) immune receptors. The regulation of TNLs via UPF1/NMD-mediated mRNA stability and translational derepression offers a dynamic mechanism for the rapid activation of TNLs in response to pathogen attack.